فاعلية طريقة الوعي الصوتي في القراءة لدى تلاميذ التربية التحضيرية دراسة ميدانية بابتدائية 1300 سكن و ابتدائية - طينة, سارة (University of Eloued جامعة الوادي, 2023)
هدفت دراستنا إلى معرفة فاعلية طريقة الوعي الصوتي في القراءة لدى تلاميذ التربية التحضيرية،حيث اعتمدنا على المنهج التجريبي بتصميم المجموعتين الضابطة و التجريبية مع القياس البعدي، وأجرينا الدراسة على عينه من تلاميذ التربية التحضيرية بابتدائية حي 1300 سكن وابتدائية جبالي جبالي السنة الدراسية 2022/2023 حيث بلغ عدد العينة 46 تلميذا مقسمة إلى مجموعتين وتم التحقق من أنهما متكافئتين في مستوى القراءة عن طريق اختبار قبلي،ثم تم تدريس المجموعة التجريبية بطريقة الوعي الصوتي في نشاط القراءة أما المجموعة الضابطة تم تدريسها بالطريقة العادية، أجرينا اختبارا بعديا بنفس معايير الاختبار القبلي على المجموعتين وأفرزت النتائج عن وجود فروق ذات دلالة إحصائية بين المجموعتين لصالح المجموعة التجريبية في القياس البعدي ومن ثم توصلنا إلى أن هناك فاعلية لطريقة الوعي الصوتي على مستوى القراءة لدى تلاميذ التربية التحضيرية. Abstract Our study aimed to know the effectiveness of the phonological awareness method on reading among preparatory education learners,where we relied on the experimental approach by designing the control and experimental groups with post-measurement,we conducted the study on a sample of preparatory education learners in the elementary school of 1300 housing district and Jabali Jabali Jabali elementary school for the academic year 2022/2023,where the sample number reached 46 learners,was divided into two groups,it was verified that they are equal in reading level through a pre-test then teaching the experimental group by the method of phonological awareness in the activity of reading. As for the control group,it was taught in the normal method,we conducted a post-test with the same criteria as the pre-test on the two groups,in fact the results revealed that there were statistically significant differences between the two groups in favor of the experimental group in the post-measurement, moreover we concluded that there is an effectiveness of the phonological awareness method on the level of reading among preparatory education learners.
تخصص علم نفس